Dual mode mobile robot : application using matlab GUI - Ahmad, Saifullah (2008)
Dual mode mobile robot has hardware and software part. For the software part, we use MATLAB GUI and for the hardware, it consists PIC 16F877A, sensor, LCD, relay and others. There are two mode to control the mobile using PIC 16F877A by interfacing with MATLAB GUI. The two modes are manual and autonomous mode. For the manual we control the mobile with GUI. For the autonomous mode, distance sensor is use to control the mobile and stop the mobile with certain distance that we have set up. The distance will display on LCD at hardware. Rs232 cable is use to connect hardware with software (PC). This project is focus on interfacing MATLAB software and hardware using rs232 cable. A graphical user interface (GUI) is a graphical display that contains devices, or components, that enable a user to perform interactive tasks. To perform these tasks, the user of the GUI does not have to create a script or type commands at the command line. Often, the user does not have to know the details of the task at hand. A PIC Microcontroller chip combines the function of microprocessor, ROM program memory, some RAM memory and input-output interface in one single package which is economical and easy to use.